The Forgotten Luther II : Reclaiming the Church's Public Witness - Cumming, Ryan P. (Book collections on Project MUSE., 2019)
In this critical time in history, this volume argues that what is urgently needed is a cogent, clear, biblically based and theologically grounded rationale for the manner in which the church speaks and acts in the political arena. Lured at times into other-worldly quietism because of the pressure of historical events or distorted through a rigid understanding of the two kingdoms, the church of the Reformation has at times been silent in addressing the political factors that create and contribute to hunger, injustice, and war. This book looks carefully at the public witness of Martin Luther and its meaning for preaching, teaching, and carrying out public ministry today. Luther's conviction was that government is responsible to God for containing evil and maintaining peace and good order, and for ensuring that no person is hungry or in want. The book asks critical questions: When should the church support the state's agenda? When should it resist? What are the options for critical but constructive cooperation? This helpful volume includes essays from leading Lutheran theologians, a summary description of what this means for local ministry, and a study guide to encourage conversation and action.